Design, Development, and Optimization of Novel Proniosomes for Enhanced Transdermal Delivery of Eprosartan Mesylate - Anitha, Dr. P. (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The present novelty in the fabrication work is preparation of proniosomal gel using eprosartan mesylate using coacervation phase separation technique. Materials and Methods: In the present work made, the formulations were prepared using drug along with excipients such as span 60, tween 80, lecithin, cholesterol, carbopol 934, alcohol, and glycerin. A total of six formulations on gels were prepared by coding EF1 to EF6. The drug and polymer interaction studies by Fourier transform infrared (FTIR) were carried before formulating the preparation composition. The gel formulations were evaluated for physicochemical evaluation such as scanning electron microscopy, percentage entrapment efficiency (EE), pH, rheological measurements, homogeneity, extrudability, spreadability, and in vitro drug release study. Results and Discussion: The formulation EF3 which was composed with drug, eprosartan mesylate 60 mg, lecithin 450 mg, cholesterol 100 mg, alcohol 0.5 mg, and carbopol 934 - 2% has shown optimum release in concentration independent manner. The in vitro drug release profile for formulation EF3 at 24 h was 98.43% and shown maximum drug release from the gel. The % EE was 89.43 ± 1.57, pH 7.04 ± 0.15, viscosity 35.46 (Pa S), and the shape, surface, and size characteristics of the optimized formulation EF3 were observed under a scanning electron microscope. The structure of the formed vesicle was studied by spreading as a thin layer on a glass slide. The images were taken using a Fujifilm Finepix F 40 fd 8.3 MP computer camera with a 3-inch optical zoom. Conclusion: Hence, prepared proniosomal gel of eprosartan mesylate could be promising drug delivery as they minimize the dose, overcome the side effects, simplify treatment regimen, and improve patient compliance